3D printed linear soft multi-mode actuators expanding robotic applications - Drury, Ryan (2022)
Soft pneumatic actuators can produce a range of motions and deliver a high force-to-mass ratio whilst offering intrinsic compliance. Presently, the majority of soft pneumatic actuators are used to create bending motions, with very few able to produce significant linear movements. Fewer can actively produce strains in multiple directions. The purpose of this study is to produce and characterize a novel 3D printed actuator which is capable of both extension and contraction under differential pressures. A new elastomeric resin was synthesized to be used on digital light projection (DLP) 3D printers. The presented pneumatic device, a linear soft multi-mode actuator (LSOMMA), is demonstrably scalable and provides a stable response over its lifetime of >10 000 cycles. The LSOMMA operates at low pressures, achieving full contraction and expansion at gauge pressures of -25 kPa and 75 kPa, respectively, corresponding to actuator strains of up to -50% and 37%. All actuators presented in this study had a rise time of less than 250 ms. The applications of these multi-mode actuators were demonstrated by developing a pipe-crawling robot capable of traversing horizontal, vertical, and bent sections of a pipe, and a ground locomotion robot capable of moving up to 652 mm min-1 and turn at 361° min-1. An untethered locomotion robot which could navigate multiple surface materials was assembled to demonstrate the potential of the developed technologies for autonomous robotic applications.